The concept of a document in jurisprudence - V. S. Sezonov (Law and Safety)
At the present stage of development of legal document science and forensic document research techniques there is a need to expand the concept of the document using the achievements of various fields of knowledge. A document is a multifaceted, generalized concept for all important sources of information. Today, there is no consensus on the classification of legal documents. In our opinion, a document in jurisprudence has the following properties: it is a carrier and source of necessary information, it is in the documents that information is recorded for the first time; has a legal meaning, economic significance, can serve as written evidence, a means of certifying something; allows you to save and extract from the archives, if necessary, information and its processing in the current activities. As the main unit of clerical correspondence, the document performs certain functions and must meet certain requirements for conclusion. All documents according to the method of presentation of the material are divided into documents with a low level of standardization and documents with a high level of standardization. Legal documents in electronic form have a completely different nature. The information that constitutes the essence of an electronic document is limited to the term "file", which in the scientific literature means a specific place on a computer medium with its own specific name. In addition, an electronic document can exist both in the form of a single file (a set of files) and in the form of a link (on the Internet). Therefore, it is considered appropriate to define a legal document as a material object with information recorded on it, which is meaningful for the establishment of legal circumstances and exists in appropriate forms and forms. A legal document is an information object that is compiled in accordance with legal requirements and contains legal information (confirmation of rights, obligations or confirmation of legal facts, events or actions that give rise to certain rights and obligations). The main ways to modernize the current legal norms and provisions relating to legal documents and records are to approve new types of legal documents in electronic form as having the same legal force as paper. Certain provisions require approval of their scope and responsibility for their protection.